2005
DOI: 10.1007/s10815-005-5147-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the number of veins ligated in a varicocelectomy with testicular volume, hormonal levels and semen parameters outcome

Abstract: Purpose : Correlate semen analysis, hormones, and testicular volume with the number of veins ligated. Methods : Patients were divided into three groups: Group 1 (≤5 veins), Group 2 (6-10 veins), and Group 3 (>10 veins). We evaluated testicular volume, hormonal levels, sperm concentration, and motility before and after the surgical procedure. Results : In Group 1, even though there was an improvement in both testicular volume and sperm concentration; testosterone levels and sperm motility did not improve with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Recent studies have shown that the total number of veins ligated has a statistically significant positive correlation with improvements in total sperm motility and sperm concentration (18,19). These results suggest that ligating a larger number of veins should lead to a greater decrease in the reflux, which in turn would lead to diminished insult to spermatogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that the total number of veins ligated has a statistically significant positive correlation with improvements in total sperm motility and sperm concentration (18,19). These results suggest that ligating a larger number of veins should lead to a greater decrease in the reflux, which in turn would lead to diminished insult to spermatogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Pasqualotto et al. [25] reported that postoperative serum TT increases were limited to patients who had more than 10 veins ligated during varicocelectomy. The clinical grade and the vein diameter might not be the determining factors for how varicocele affects testicular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Shindel et al [27] suggested that the number of ligated veins is positively correlated with an increase in sperm motility. Pasqualotto et al [28] reported that patients with more than 10 ligated veins at the time of varicocelectomy have better chances of showing an improvement in sperm concentration. In the present study, the presence of more than 9 ligated veins was a good prognostic factor for successful varicocelectomy.…”
Section: Discussionmentioning
confidence: 99%